Messages from the President and the Coordinator, Committees and Speakers: Volume 8 - Number 3 - 2017 - Jurno, Mauro Eduardo; Valle, Ricardo Tanus (Headache Medicine, 2017)
XXXI Congresso Brasileiro de Cefaleia e XII Congresso de dor orofacil